(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The study investigates the development and assessment of individualized oral hygiene measures for patients undergoing orthodontic treatment. Orthodontic appliances often complicate daily oral care, increasing the risk of plaque accumulation, gingival inflammation, and dental caries. This research aims to design personalized hygiene protocols tailored to the needs of orthodontic patients and to evaluate their effectiveness in improving oral health outcomes. The study involved a sample of patients undergoing fixed orthodontic treatment, with interventions including individualized instruction on brushing techniques, interdental cleaning, and the use of auxiliary oral hygiene tools. Evaluation was performed using clinical indices of plaque accumulation, gingival health, and patient adherence.